Structural changes in Psidium guajava 'Paluma' leaves exposed to tropospheric ozone - Tresmondi,Fernanda (2011)
Psidium guajava 'Paluma' has being tested as an ozone (O3) bioindicator and responds with pigmentation between the veins on the adaxial surface, due to the accumulation of phenolic compounds. These compounds act as non-enzymatic antioxidants that neutralize reactive oxygen species (ROS), formed from O3. This study aimed to evaluate the leaf structure of plants with and without visible symptoms and to establish these symptoms at the cellular level. Beside this we also aimed to detect structural changes that can minimize the effects of the O3 on the plant. The accumulation of phenolic substances, stomatal density and structural changes in P. guajava 'Paluma' leaf tissues exposed during the four seasons of the year were evaluated. The study was conducted at the Parque Estadual das Fontes do Ipiranga ( PEFI), which is a park in the city of São Paulo that has high levels of O3. Leaves with symptoms showed, on the adaxial surface, anthocyanin accumulation in the vacuoles of epidermal cells and hypodermis. When the symptoms were more intense this accumulation was observed even in the first three layers of palisade parenchyma. Comparing symptomatic and asymptomatic leaves, there was higher accumulation of phenolic compounds in the symptomatic leaves. Some parenchyma cells adjacent to substomatal chambers showed intrusive growth towards the stomatal pore, promoting its occlusion, which could reduce the entry of O3 in the leaf. The accumulation of anthocyanins and other phenolic compounds, in addition to the occlusion of the chamber, protect the plant against O3 effects. These features and the compact arrangement of the mesophyll contribute to why Psidium guajava 'Paluma' does not present cell death, a symptom usually observed in species sensitive to O3.